"Determinants of Dividend Payout Ratio: Empirical Evidence from Ethiopian Private Banks" - Mr. Birhan Moges Adugna, Dr. Getaneh Mhiret, Dr. Bhupendra Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study empirically examines the effect of firm specific and macroeconomic factors on dividend payout decision of the Ethiopian private commercial banks. Using panel data on eight private banks covering 2008 – 2016, the random-effect regression model results revealed that liquidity, bank size and inflation have positive and statistically significant impacts on dividend payout decision. But, the regression results suggest that bank’s growth and investment opportunity have negative and statistically significant impact on dividend payout decision in Ethiopian private banks.